Assessment of h-index and associated demographic and academic parameters for academic hematologists in Canada - Ordaz, Daniel Josué Guerra; Roy, Jean; Ahmad, Imran; Kaouache, Mohammed; Ramchatesingh, Brandon; Whitelaw, Sera; Nikonova, Anna; Bredeson, Chris; Litvinov, Ivan V. (Frontiers in Medicine, 2024)
Introduction: The h-index measures researchers’ productivity by assessing simultaneously the number of publications and citations. We aimed to assess the factors that could influence h-index for hematologists practicing in academic institutions in Canada. Methods: We identified universities with a hematology residency training programs/fellowships using the Canadian Resident Matching Service (CaRMS) website. We obtained the listing of faculty, sex, and academic ranks by consulting faculty directories or by contacting respective departments/universities, when directories were unavailable or incomplete. For each faculty member, we obtained years since Royal College of Physicians’ and Surgeons of Canada certification or equivalent, receipt of Canadian Institute of Health Research (CIHR) grants within the last 5 years, attainment of graduate degrees (M.Sc., Ph.D., other), and the h-index. Results: The data included information collected from 372 individuals (171 females) across Canada (Atlantic Provinces: 13; Quebec: 89; Ontario: 182; Prairie Provinces: 59; British Columbia: 29). Univariate analysis showed that male sex, practicing in British Columbia, longer duration since specialty certification, completion of an M.Sc. or a Ph.D. degree, attaining a higher academic rank and receiving CIHR funding were associated with higher h-index.The results of the univariate analysis were concordant with the multivariate analysis, except that practicing in Ontario was also associated with higher h-index. Conclusions:This study provides details on the h-index curve/parameters for academic productivity of hematologists in Canada. Importantly, based on multivariate analysis, higher h-index was associated with male sex, location of practice, years since certification, attainment of M.Sc. or Ph.D. degrees, academic rank, and recent CIHR funding.